Sustentabilidade territorial urbana : uma análise conceitual - Sampaio, Danusa Teodoro (2010)
The emergence of the term "sustainability" practiced in the world from the 80 end has been replaced by an extensive design, based on the appropriation and politicization that academically involved in the maturation studies in order to provide a more defined space for discussion of theory and practice in public policies aimed at sustainability. The main objective of the research was to analyze the concepts of urban sustainability and identifying convergences and divergences found in the literature. The general strategy used research was the literature review for this study have probing nature on a theme still insufficient, especially with regard to different approaches to territorial urban sustainability. The general steps of the research are: 1 choice of authors who discuss the terms of sustainable development, sustainability, political ecology, rural urban sustainability, moderate environmentalism, until reaching the border of interest, territorial urban sustainability; 2- analysis of the terms and concepts discussed by each author; 3- analysis of the discussion advance in chronological order; 4 collation and analysis of convergence of discussions between authors; 5- analysis of the differences in terms and concepts. They were used as evidence sources to consult the books, electronic articles, academic papers, magazines and other materials of literary sources published in tangible media and intemet, able to bring relevant information to the realization of this study. The results refer to: 1- analysis of how each author appropriated the terms and concepts; 2- definition of each concept discussed; 3- discussions of convergence of identification; 4- advance the discussions in chronological order; 5- amflise divergences between authors, terms and concepts. The results indicate that the use of terms and concepts allows derivations as each form of ownership and still have the other dimensions of lifting sustainability can be discussed, but that are not easily identified in the literature.